O krok dalej w przybliżeniu słowa Bożego. Poznańscy bibliści w służbie orędziu Starego i Nowego Testamentu. - Nawrot, Janusz (Poznańskie Studia Teologiczne, 2020)
On the occasion of 100 years of existence and activity of Adam Mickiewicz University in Pozna, one may sum up the contribution of the Faculty of Theology which has existed as part of the uni- versity for 20 years. This contribution has concerned the research and teaching arenas combined with a commitment for the social community of the Wielkopolska province. What is specific of the faculty is its ability to work both on the scientific and didactic levels as well as on the church level, which requires considerable knowledge and time in order to competently combine the requirements of working at university with demands of the Catholic Church managed by the Second Vatican Council. The scientific and popular scientific initiatives in the widely understood biblical studies represent a valuable contribution to the celebration of 100 years of the Pozna university. Like other scientific disciplines, they can proudly make their own contribution to the development of sci- ence in our city, as well as the entire country. One can only hope that the present generation of sci- entists will take the baton passed to them in the relay race of generations, and will make their own contribution to the science thereby honouring Pozna as an important scientific centre in Poland.